Evaluation of hysteroscopy as a complementary exam in the investigation of chronic pelvic pain. - Meneses Dias, Bruno Hállan; Rodrigues de Andrade, Ana Carolina; Holanda Pascoal da Silva, Angélica Maria; de Vasconcelos Filho, Francisco Eugênio; Parente Paiva, Jordana; das Chagas Medeiros, Francisco (Journal of Health & Biological Sciences, 2013)
Introduction: Chronic pelvic pain (CPP) is a difficult condition to identify and many disorders are correlated. This study investigates the role of hysteroscopy as a complementary exam in the diagnosis of CPP. Methods: One hundred ninety-one medical records of women with indication to perform a hysteroscopy and presented CPP were reviewed. Results: The analysis showed abnormalities in 99 patients. Of these, more than 70% presented conditions that could cause CPP. Cervical stenosis and findings suggestive of adenomyosis were the most frequent ocurrences. Conclusions: Hysteroscopy is useful to detect pathological conditions of the cervix and uterine cavity that may coexist with chronic pelvic pain.